Pengaruh Pola Asuh Terhadap Kejadian Stunting Dan Perkembangan Balita Usia 24-59 Bulan Di Desa Pulo Lor Kecamatan Jombang Kabupaten Jombang - Ningtyas, Septi Fitrah; Mudhawaroh, Mudhawaroh; Diana, Rini Nur; Hadi, Selasih Putri Isnawati (ARTERI : Jurnal Ilmu Kesehatan, 2025)
Stunting is a chronic nutritional condition that impairs child growth and development, particularly during critical physical formation periods. Among various factors influencing toddler growth and stunting incidence, parenting style is a significant determinant. This study aimed to determine the influence of parenting styles on stunting incidence and the development of toddlers aged 24–59 months in Pulo Lor Village, Jombang Regency. A quantitative study with a cross-sectional analytic design was conducted. A sample of 54 toddlers was selected using a purposive sampling technique. Data were collected using anthropometric measurements and questionnaires, and subsequently analyzed using Linear Regression to assess the correlation between parenting styles, stunting rates, and child development. The results showed that the majority of respondents (74.1%, n=40) applied a democratic parenting style. Most toddlers (n=43) were not stunted, and 74.1% (n=40) demonstrated appropriate development. The statistical analysis yielded a p-value of 0.000 (p < 0.05). It is concluded that there is a significant influence of parenting style on stunting incidence and toddler development in the study area. Stunting prevalence and toddler development are strongly associated with parenting styles. Enhancing parental knowledge and support is crucial to prevent stunting and promote healthy growth, particularly regarding caregiving, nutrition, and developmental stimulation.